A 14-Marker Multiplexed Imaging Panel for Prognostic Biomarkers and Tumor Heterogeneity in Head and Neck Squamous Cell Carcinoma - Mitsuda, Junichi; Tsujikawa, Takahiro; Yoshimura, Kanako; Saburi, Sumiyo; Suetsugu, Masaho; Kitamoto, Kayo; Takenaka, Mari; Ohmura, Gaku; Arai, Akihito; Ogi, Hiroshi; Itoh, Kyoko; Hirano, Shigeru (Frontiers in Oncology, 2021)
Recent advances made in treatment for head and neck squamous cell carcinoma (HNSCC) highlight the need for new prediction tools to guide therapeutic strategies. In this study, we aimed to develop a HNSCC-targeting multiplex immunohistochemical (IHC) panel that can evaluate prognostic factors and the intratumor heterogeneity of HNSCC. To identify IHC-based tissue biomarkers that constitute new multiplex IHC panel, a systematic review and meta-analysis were performed to analyze reported IHC biomarkers in laryngeal and pharyngeal SCC in the period of 2008–2018. The Cancer Genome Atlas (TCGA) and Reactome pathway databases were used to validate the prognostic and functional significance of the identified biomarkers. A 14-marker chromogenic multiplex IHC panel including identified biomarkers was used to analyze untreated HNSCC tissue. Forty-five high-quality studies and thirty-one candidate tissue biomarkers were identified (N = 7062). Prognostic validation in TCGA laryngeal and pharyngeal SCC cohort (N = 205) showed that β-catenin, DKK1, PINCH1, ADAM10, and TIMP1 were significantly associated with poor prognosis, which were related to functional categories such as immune system, cellular response, cell cycle, and developmental systems. Selected biomarkers were assembled to build a 14-marker panel, evaluating heterogeneity and polarized expression of tumor biomarkers in the tissue structures, which was particularly related to activation of Wnt/β-catenin pathway. Integrated IHC analysis based on a systemic review and meta-analysis provides an in situ proteomics tool to assess the aggressiveness and intratumor heterogeneity of HNSCC.